2008
DOI: 10.1055/s-2008-1062269
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Myopathies and Muscular Dystrophies

Abstract: The inherited myopathies and muscular dystrophies are a diverse group of muscle diseases presenting with common complaints and physical signs: weakness, motor delay, and respiratory and bulbar dysfunction. The myopathies are caused by genetic defects in the contractile apparatus of muscle, and defined by distinctive histochemical or ultrastructural changes on muscle biopsy. The muscular dystrophies, in contrast, are diseases of muscle membrane or supporting proteins, which are generally characterized by pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 62 publications
0
37
0
5
Order By: Relevance
“…CK-nivået er ofte betydelig forhøyet ved mange av muskeldystrofiene, men bare lett forhøyet eller normalt ved de arvelige myopatiene (1). Muskeldystrofiene affiserer muskelcellemembranene eller andre strukturer som fører til nedbryting av muskelfibre.…”
Section: Christoffer Jonsrudunclassified
See 1 more Smart Citation
“…CK-nivået er ofte betydelig forhøyet ved mange av muskeldystrofiene, men bare lett forhøyet eller normalt ved de arvelige myopatiene (1). Muskeldystrofiene affiserer muskelcellemembranene eller andre strukturer som fører til nedbryting av muskelfibre.…”
Section: Christoffer Jonsrudunclassified
“…For de aller fleste arvelige nevromuskulaere tilstander finnes ingen spesifikk behandling mot prosessene i muskler eller nerver (1,3,8). Dette gjelder også muskeldystrofier som skyldes mutasjoner i LMNA-genet.…”
Section: Diskusjonunclassified
“…1 Schwere Formen (bis zum "floppy infant"-Syndrom) einer kongenitalen Myopathie mit Cores (u. a. MultiminicoreMyopathie) werden autosomal-rezessiv vererbt und zeigen 2 Mutationen im RYR1-Gen, die häufig nicht in den Mutations-Hot-Spots liegen. Neuerdings konnte auch gezeigt werden, dass eine rezessive Keimbahnmutation genügt, wenn das materne RYR1-Allel im Muskelgewebe durch epigenetische Mechanismen abgeschaltet ist [13].…”
Section: Diagnostikunclassified
“…Die individuellen Mutationen sind über das ganze Gen verstreut, ohne klaren Hinweis auf eine Genotyp-Phänotyp-Korrelation. Über die Funktion des Proteins im Muskel ist wenig bekannt; Myoblastenzellkulturen ohne SEPN1-Expression sind sehr anfällig für oxidativen Stress ( [8], Über-sichten bei [1,3,6,8,12]). …”
Section: Diagnostikunclassified
“…Genetic muscle disorders are a diverse group of hereditary disorders that present with muscle weakness, cause significant comorbidities and result in reduced daily functioning [1]. It has been shown that a substantial proportion of people living with a chronic illness are affected by a genetic muscle disease [2].…”
Section: Introductionmentioning
confidence: 99%